Taxonomic revision of Cyphanthidium Pasteels (Hymenoptera: Apoidea: Megachilidae: Megachilinae: Anthidiini), an endemic Afrotropical bee genus - Eardley, Connal; Griswold, Terry (Zootaxa, 2018)
The Afrotropical bee genus Cyphanthidium Pasteels is revised. It comprises four species. Cyphanthidium gessorum, new species, and Cyphanthidium whiteheadi, new species, are described as well as the previously unknown female of Cyphanthidium intermedium. A key for identifying the species is given. Supplemental information is provided on the recently published revisions of Serapista and Plesianthidium.